Sankcje w rolnictwie ekologicznym - Leśkiewicz, Katarzyna (Wydawnictwo Naukowe UAM, 2010)
The aim of this paper was to discuss to what degree sanctions ensure compliance of ecological production with the requirements specified in the binding legal regulations. The author analyses negative consequences imposed in case of infringement of requirements of organic farming and presents their classification. Sanctions applied in organic farming include fines and other measures. In the conclusion the author states, among other things, that sanctions in organic farming need to be evaluated particularly in view of the criteria indicated by the legislator, i.e. in terms of their effectiveness, whether they are commensurate with the offence and whether they are deterrent. The legal regulation of these sanctions to a considerable degree is to ensure that organic products have characteristics specified by the EU regulations. However, it needs to be remembered that sanctions only supplement the system of control in organic farming and the quality of organic products (their compliance with the requirements specified in binding regulations) is determined definitely by actions of producers and certifying bodies.

Lo studio si propone l’obiettivo di formulare la risposta alla domanda sulla capacità delle sanzioni a garantire la conformità della produzione biologica ai requisiti determinati dal legislatore. L’Autrice effettua un’analisi delle conseguenze negative per la violazione delle norme relative all’agricoltura biologica, e distingue, la pena pecuniaria dalle altre misure. In conclusione l’Autrice afferma, tra l’altro, che le sanzioni nell’agricoltura biologica devono essere valutate soprattutto attraverso i criteri indicati dal legislatore, cioè in relazione alla loro efficacia, proporzionalità, e capacità di dissuasione. La regolazione giuridica delle sanzioni contribuisce in modo notevole ad assicurare che i prodotti biologici possiedano le qualità determinate dal legislatore comunitario. Tuttavia occorre ricordare che sanzioni servono soltanto a completare il sistema del controllo nell’agricoltura biologica. Invece la qualità dei prodotti biologici (la loro conformità ai requisiti previsti dal legislatore) è determinata in modo definitivo attraverso le azioni del produttore e degli organismi di certificazione.